FEATURES OF USING AMAZON INSPECTOR TO IDENTIFY VULNERABILITIES OF CLOUD APPLICATIONS - Partyka, Andrii; Nedodus, Bohdan (Ukrainian Information Security Research Journal, 2024)
Vulnerability to various cyber-attacks, loss of data confidentiality, increased number of failures and reduced stability of information infrastructure, increased capital costs, new requirements for data independence, problems with scaling business information infrastructure can be the main problems that a business may face. The above-mentioned problems can serve as a basis for migration to cloud technologies, which in turn will ensure a reduction in expenses for infrastructure support, increase the efficiency of information infrastructure management compared to work in a local environment, and increase the flexibility of the organization. The relevance of the research lies in improving information security, ensuring confidentiality, integrity and availability, identifying application and environment vulnerabilities through the use of built-in AWS services. The purpose of this work is to implement the evaluation and improvement of the security of the working environment and the application deployed on the basis of cloud services by automating the scanning and analysis of the AWS workload.